Resilience training in a restructuring organization : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in Psychology, Massey University - Bullen, Heather Leanore (Massey University, 2006)
The aim of the present research was to investigate the extent to which resilience training helped to minimize employee stress levels and improve wellbeing during a time of organizational change. The 33 employees involved in this study consisted of three groups. Group 1 received resilience training in 2002 and 2003; Group 2 received resilience training in 2003; and Group 3, the control group, received no resilience training during this study. A baseline measure of stress and wellbeing was collected for all groups before the start of the 2003 resilience training (Time 1, April) and repeated after the resilience training (Time 3, November). Data was also collected on the resilience variables of curiosity and coping at Time 2 (August) and repeated at post training (Time 3, November). The 2003 restructuring was consistent for all groups at Time 1 (April) but subsequent changes during the year impacted more heavily on the resilience trained groups. The results showed that group 1 (Trained in 2002) reported significantly less somatic distress than the other two groups at baseline (Time 1). While none of the hypothesized differences were found at Time 3, the resilience trained groups showed low stress levels and good wellbeing levels despite the organizational stressors. All groups showed reasonable levels of resilient coping and low levels of non-resilient coping at both times. The research shows some support for the effectiveness of the resilience training, although the results are interpreted with caution due to the small sample size and the different exposure to work stressors of the control group. Further research on resilience is recommended.
Keywords: Resilience; Corporate re-organisation; Organisational change; Employee training; Employee stress; Resilience training